Response to adjuvant chemotherapy in primary breast cancer: no correlation with expression of glutathione S-transferases. - Peters, W. H. (Nature Publishing Group, 1993)
Of 139 node-positive breast cancer patients treated with adjuvant chemotherapy, the pre-treatment levels of glutathione S-transferase (GST) classes alpha, mu and pi, were determined by immuno-quantification on Western blots in cytosols of the primary tumours. Their expression was studied with respect to cytosolic oestrogen-receptor, progesterone-receptor and cathepsin D levels, and to the length of disease-free survival. GST class pi was negatively correlated with oestrogen receptor and progesterone receptor, and positively correlated with cathepsin D. There was no correlation between GST isoenzymes and the length of disease-free survival. These data suggest that glutathione S-transferases are not useful as markers to predict the response to adjuvant chemotherapy in human breast cancer. IMAGES: